2013
DOI: 10.1093/cercor/bht137
|View full text |Cite
|
Sign up to set email alerts
|

Neural Language Processing in Adolescent First-Language Learners

Abstract: The relation between the timing of language input and development of neural organization for language processing in adulthood has been difficult to tease apart because language is ubiquitous in the environment of nearly all infants. However, within the congenitally deaf population are individuals who do not experience language until after early childhood. Here, we investigated the neural underpinnings of American Sign Language (ASL) in 2 adolescents who had no sustained language input until they were approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 88 publications
7
25
0
Order By: Relevance
“…While prior studies have not found right IPS to be modulated by language proficiency, the participants in those studies have typically possessed higher proficiency in L2 (Leonard et al, 2010, 2011). In case studies of deaf signers with scant proficiency in any language, we have observed right IPS activation later at 300–350 ms (Ferjan Ramirez et al, 2013a). It is possible that modality and proficiency interact in parietal regions, perhaps reflecting a neural processing strategy that is uniquely useful for the dynamic visual linguistic content of sign languages.…”
Section: Discussionmentioning
confidence: 84%
“…While prior studies have not found right IPS to be modulated by language proficiency, the participants in those studies have typically possessed higher proficiency in L2 (Leonard et al, 2010, 2011). In case studies of deaf signers with scant proficiency in any language, we have observed right IPS activation later at 300–350 ms (Ferjan Ramirez et al, 2013a). It is possible that modality and proficiency interact in parietal regions, perhaps reflecting a neural processing strategy that is uniquely useful for the dynamic visual linguistic content of sign languages.…”
Section: Discussionmentioning
confidence: 84%
“…Without PFS, their communication system could include nouns, verbs, adjectives, numbers, color and size modifiers, but was void of spatial prepositions, verb tenses, nesting, and other recursive elements. Neanderthal communication system was similar to the communication system used by contemporary individuals who have fluid speech combined with PFS disability: individuals with prefrontal aphasia (Cole et al 2014, Fuster 2008, specific brain damage (Ditunno and Mann 1990, Gläscher et al 2009, Heremans et al 2012, Kosslyn et al 1985, Waltz et al 1999, late first-language learners (Emmorey et al 1993, Martin 2009, Martin et al 2013, Pyers et al 2010, and verbal low-functioning individuals (Matson andShoemaker 2009, Vyshedskiy et al 2019).…”
Section: Neanderthal Speech Culture and Hunting Stylesmentioning
confidence: 96%
“…PFS disability is not limited to individuals with LPFC damage. Individuals without any brain injury exhibit PFS disability if they were not exposed to recursive language in early childhood (Emmorey et al 1993, Martin 2009, Martin et al 2013, Pyers and Senghas 2009). In our meta-analysis of published research, ten out of ten individuals linguistically deprived until puberty suffered lifelong PFS disability despite learning significant vocabulary through intensive post-pubertal language therapy (Vyshedskiy et al 2017b).…”
Section: Use Of Recursive Language In Early Childhood Is Necessary Fomentioning
confidence: 99%
See 2 more Smart Citations